Revisão taxonômica de Thoracocharax Fowler, 1906 (Characiformes, Gasteropelecidae), com a descrição de duas novas espécies. - Souza, Fagner de (2014)
Thoracocharax is a genus belonging to the family Gasteropelecidae, with two valid species, which are distributed throughout the South America, in the basins of Paraná-Paraguay, Amazonas and Orinoco rivers. They have a distinctive morphology compared to other members of Characiformes, with the pectoral region forming a prominent keel, large pectoral fins, reduced pelvic fins and laterally compressed body. This morphology is associated with their capacity of leaping out of the water as an evasive strategy. In the present study we revised the genus based on material of its entire geographic distribution. Additionally to the external morphology analysis we did truss network measurements for comparisons between populations. We found that the genus is composed by four species T. stellatus, T. securis and two new species. The nominal species Gasteropelecus pectorosus, T. brevis e T. magdalenae remained as synonymous. Updated diagnoses and geographic distributions of each species are provided.